MANAUS CITY OF THE FUTSAL (Fiep Bulletin - online, 2010)
This article seeks to present a project entitled Manaus City Futsal, which is nothing more than an effective action resulting from the sports public policy used by the municipal government of Manaus, which through its municipal office for sports and leisure offers the sport futsal to children , youth and adults so that it is a means of social development, ie transforming element of the social reality of these individuals. Are presented in this study some of the concepts underlying the design, their development, some data collected in its first operational year 2010, as well as their goals for the coming year of activities.
Keywords: Policies publics sports; Development social; Futsal